PERSPEKTIF JEAN BAUDRILLARD DALAM GAYA HIDUP KONSUMTIF PENGGUNA SHOPEE PAYLATER - Simanullang, Inelda; Kayla Chelsie Anindra; Nyayu Tania Wulandari; Deni Aries Kurniawan; Vieronica Varbi Sununianti; Istiqoma (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2025)
This study examines the impact of simulacrum-based consumption, particularly in the context of Shopee PayLater usage, on consumer behavior and financial sustainability. The study identifies how consumers are influenced by promotional strategies and social status rather than actual financial capacity. The research employs a qualitative approach by analyzing user behavior patterns and financial implications of installment-based consumption. The findings indicate that Shopee PayLater fosters an illusion of ownership, leading to increased consumer debt and a lack of financial awareness. Additionally, the study highlights a shift in consumer habits from necessity-driven purchases to image-based consumption. The conclusion emphasizes the importance of financial literacy to mitigate excessive reliance on digital credit services. The study suggests that both consumers and e-commerce platforms should take a more responsible approach to financial management to prevent long-term financial instability.